Trait Expression and Environmental Responses of Pea (Pisum sativum L.) Genetic Resources Targeting Cultivation in the Arctic - Carlson-Nilsson, Ulrika; Aloisi, Karolina; Vågen, Ingunn M.; Rajala, Ari; Mølmann, Jørgen B.; Rasmussen, Søren K.; Niemi, Mari; Wojciechowska, Ewelina; Pärssinen, Pertti; Poulsen, Gert; Leino, Matti W. (Frontiers in Plant Science, 2021)
In the Arctic part of the Nordic region, adverse and extreme climate conditions, such as low temperatures, long days and a short growing season, require specific adaptations in cultivated crops. Under projected climate change scenarios, higher temperatures and an earlier spring thaw will gradually allow the cultivation of plants that could not previously be cultivated there. Pea (Pisum sativum L.) has been a major cultivated protein plant in Nordic countries for millennia but is currently limited to the region’s southern parts. However, a response and adaptation to the Arctic day length/light spectrum and temperatures are essential for productivity of the pea germplasm and need to be better understood. This study investigated these factors and identified suitable pea genetic resources for future cultivation and breeding in the Arctic region. Fifty gene bank accessions of peas with a Nordic landrace or cultivar origin were evaluated in two-year field trials at four Nordic locations in Denmark, Finland, Sweden and Norway (55° to 69° N). The trial sites’ contrasting environmental conditions revealed differences in expression of phenological, morphological, crop productivity and quality traits in the accessions. The data showed that light conditions related to a very long photoperiod partly compensated for the lack of accumulated temperature in the far north. A critical factor for cultivation in the Arctic is the use of cultivars with a rapid flowering and maturation time and early sowing. At the most extreme site (69 °N), no accession reached full maturation. Nonetheless several accessions, predominantly landraces of a northern origin, reached a green harvest state. All the cultivars reached full maturation at the sub-Arctic latitude in northern Sweden (63 °N) when plants were established early in the season. Seed yield correlated strongly with seed number and aboveground biomass, but negatively with flowering time. A high yield potential and protein concentration of dry seed were found in many garden types of pea, confirming their breeding potential for yield. Overall, the results indicated that pea genetic resources are available for breeding or immediate cultivation, thus aiding the northward expansion of pea cultivation. Predicted climate changes would support this expansion.